2022
DOI: 10.2147/pgpm.s369556
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Predictive Model for Dermatomyositis Associated with Rapidly Progressive Interstitial Lung Disease

Abstract: Background Rapidly progressive interstitial lung disease (RP-ILD) is a significant complication that determines the prognosis of dermatomyositis (DM). Early RP-ILD diagnosis can improve screening and diagnostic efficiency and provide meaningful guidance to carry out early and aggressive treatment. Methods A retrospective screening of 284 patients with DM was performed. Clinical and laboratory characteristics of the patients were recorded. The risk factors of RP-ILD in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition to its association with ILD, several studies have linked anti-Ro52 with RP-ILD, a progressive subtype of ILD with a high mortality rate and resistance to treatment 12. We showed that anti-Ro52-positive patients had 2.69 times higher odds of having RP-ILD than anti-Ro52-negative subjects.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In addition to its association with ILD, several studies have linked anti-Ro52 with RP-ILD, a progressive subtype of ILD with a high mortality rate and resistance to treatment 12. We showed that anti-Ro52-positive patients had 2.69 times higher odds of having RP-ILD than anti-Ro52-negative subjects.…”
Section: Discussionmentioning
confidence: 67%
“…A higher OR shows that patients with positive anti-Ro52 were more likely to have simultaneous RP-ILD. 12 13 16 27 34 35 40 47 77–79…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single indicator fails to accurately predict a particular outcome, owing to limited predictive value; however, a prediction model incorporating several relevant risk factors may serve as a useful tool to enhance predictive power. To date, many prediction models associated with MDA5+ DM or RP-ILD have been established [ 6 , 17 21 ]. In their study, So et al proposed a prediction model in MDA5 + DM patients consisting of fever, lactate dehydrogenase, age, and neutrophil-to-lymphocyte ratio to stratify the risk of the RP-ILD complication [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous ulcers (ulcerated or inverted Gottron papules) are also associated with an increased risk of this complication [3]. Patients with positive anti-MDA5 and anti-Ro52 antibodies, especially in high titers as seen in case 1, have a higher risk of rapidly progressive-interstitial lung disease and a lower survival rate compared to patients with only anti-MDA5 [4][5][6][7][8]. Coexistence of these antibodies may help identify a subgroup of patients with severe disease, predict prognosis, and possibly guide risk-based therapy as previously shown in very few cases.…”
mentioning
confidence: 99%